PERAN KO KURIKULER DAN EKSTRAKURIKULER TERHADAP UPAYA PENCAPAIAN KURIKULUM 2013 - Hidayah, Lutviyana (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2019)
This article aims to describe the role and concepts of co-curricular and extracurricular activities so that it is useful for achieving the goals of the 2013 curriculum. This 2013 curriculum has three important objectives, namely Strengthening Character Education, Strengthening Literacy Culture, and 21st Century Learning. This type of research is library research, research sources are found in the literature and sources, or the latest findings regarding the Curricular and Extracurricular activities as well as the 2013 Curriculum. The results of this research are that co-curricular and extracurricular activities play a major role in achieving the three aspects of learning contained in the curriculum 2013, namely cognitive, affective and psychomotor aspects. These three aspects are very helpful in achieving the 2013 curriculum agenda, which consists of character strengthening, literacy culture and 21st century learning. Character strengthening can be achieved through religious extracurricular activities, Hisbul Wathan and BTQ, Kultum, work assignments, and intensive post-school guidance. Literacy culture can be achieved by reading guidance programs both reading the Al-Qur’an or spelling, one verse a day program. 21st century learning is pursued by extracurricular activities, namely tambourine activities, calligraphy and so on. The expected positive impact of this article is the dissemination of information about the urgency of co-curricular and extracurricular activities in an educational institution to achieve learning objectives in the 2013 curriculum.